Innovation Strategy Of Village-Owned Enterprises (BUMDes) In Increasing The Potential And Economic Welfare Of The Community In Meraran Village, Seteluk Distric, West Sumbawa Regency - Lidia wati; Jalaluddin, Jalaluddin (Jurnal Ekonomi, 2024)
This Study aims to formulate an appripiate innovation strategy for BUMDesTonyongMandiri in increasing the potential and welfare of the Village Communty Economy. The research, Qualitative data collection techniques in this study using purposive sampling conducted by interview, direct observation to BUMDes administrators, Village Head, Village Facilitators, while quantiatative data obtained from Community leaders through questionnaires, then the data is analyzed descriptively using SWOT analysis. The results show that BUMDesTonyongMandiri in its management has good strengths and opportunities, but there are still many things that need to be fixed including not utilizing the potential of existing naural resources, choosing types of businesses that are less in accordance with community needs, strengthening HR capacity needs to be improved, then product marketing has not been clearly directed. The result of the SWOT Matrix analysis obtained the formulation of the BUMDesTonyongMnadiri innovation strategy. Namely: 1) Analysingthe capacity of sustainable Vilage superior products, 2) Improving the supporting facilities and inftastructure for BUMDes, 3) conducting business feasibility studies, 4) partnering wit Village superior with MSMES, farmer groups and other BUMDes, 5) Utilizing Teknology, 6) involving the Community in determining the type of business to be develoved, 7) implementing trsining and education on marketing, financial, HR, operational and production management as well as BUMDes governance.